Removal Of Methylene Blue In Textile Industry Using Activated Carbon From Mangrove Pile Leftover Via Chemical Activation - Kok, Joe Ye (Universiti Sains Malaysia, 2018)
In this research, mangrove pile leftovers which were mainly dumped as construction waste were used as the raw precursors to prepare activated carbon for methylene blue removal which could be found mainly in textile industries. The main objective of this research was to prepare activated carbons from mangrove pile leftovers via chemical activation using phosphoric acid. The effects of different factors such as impregnation ratio of phosphoric acid to precursor as well as activation temperature on the yield of activated carbon and the adsorption capacity on methylene blue were studied. Highest yield of activated carbon was obtained for preparation condition of IR of 2 and Ta of 400 'C, with yield of 34.83 %. An impregnation ratio of 2 and activation temperature of 600'C were found to be the optimum condition for activated carbon preparation since maximum adsorption capacity of 388.88 mg/g was observed. The adsorption of methylene blue on the activated carbon prepared was found to be multilayer adsorption since it fit well to Freundlich isotherm with R2of 0.9601. From perspective of kinetic study, the experimental data of adsorption of methylene blue on optimal activated carbon was fit well to Pseudo-second order model with R2of 0.9592. BET surface area, Langmuir surface area and total pore volume of the optimally prepared activated carbon were 802.3744 m2/g, 1186.3197 m2/g and 0.412336 cm3/g respectively. After the activation process, the carbon content of activated carbon was found to be increased from 59.91 to 84.68 wt% since more volatile materials were released.